Innovative packaging of fruits and vegetables : strategies for safety and quality maintenance - Rahman, Shafiur; Siddiqui, Mohammed Wasim; Wani, Ali Abas (Toronto : Apple Academic Press, 2018)
"This forthcoming volume, Innovative Packaging of Fruits and Vegetables: Strategies for Safety and Quality Maintenance, addresses the challenges of the short shelf-life of fruits and vegetables. Innovative packaging technologies are the most promising strategies for overcoming these limitations. The book will provide a host of sustainable packaging solutions that deliver protection, branding, consumer attractiveness, and speed to market in a competitive retail environment. Many new packaging technologies were developed to maintain the quality and freshness of the products, thus extending the shelf-life, reducing the food losses, and facilitating commercialization and export. Extending the shelf life by just three to four days by using an innovative packaging prevents large amounts of these perishables from spoiling during transportation and handling. When stored in an optimal atmosphere, their metabolism slows down, thus the produce remains fresh and crunchy.Innovative packaging solutions include gas controllers that can be incorporated in the packaging materials to delay senescence. Intelligent packaging, such as freshness or time-temperature indicators, monitors product quality and safety and enhances the marketing of the packaged fruits and vegetables. These new technologies require specific knowledge and appropriate training/understanding for rational in selecting the most suitable packaging for each product and intended use. "--Provided by publisher.
chapter 1 Bio-Based Packaging for Fresh Fruits and Vegetables / O. P. Chauhan K. Chitravathi lakshmi E. Unni -- chapter 2 Modified Atmosphere Packaging of Fresh Produce / Ali Abas Wani Khalid Gul Preeti Singh -- chapter 3 Active Packaging of Fresh and Fresh-Cut Fruit and Vegetables / Astrid F. Pant J. Thielmann -- chapter 4 Intelligent Packaging Applications for Fruits Andvegetables / Bambang Kuswandi -- chapter 5 Shrink Packaging of Fruits and Vegetables / D. V. Sudhakar Rao -- chapter 6 Antimicrobial Packaging: Basic Concepts and Applications in Fresh and Fresh-Cut Fruits and Vegetables / BasharatYousuf Ovais Shafiq Qadri Abhaya Kumar Srivastava -- chapter 7 Edible Coatings and Their Effect on Postharvest Fruit Quality / K. Prasad M. W. Siddiqui R. R. Sharma Abhay Kumar Gaurav Pallavi Neha Nirmal Kumar -- chapter 8 Packaging Of Fresh-Cut Fruits and Vegetables / Oluwafemi j. Caleb martin geyer pramod v. Mahajan -- chapter 9 Engineering Properties of Packaging Films / Stefano Farris -- chapter 10 Predictive Modeling for Packaged Fruits and Vegetables / Amit Kumar Shubhra Shekhar Kamlesh Prasad -- chapter 11 Mathematical Modeling for Micro-Perforated Films of Fruits and Vegetables Used in Packaging / Oluwafemi j. Caleb martin geyer Pramod v. Mahajan -- chapter 12 Cushioning Materials for Fruits, Vegetables, and Flowers / Neeru Dubey Vigya Mishra -- chapter 13 Nano-Enabled Packing of Food Products / Vigya Mishra Neeru Dubey Simple Kumar Neha Singh.
Keywords: Food -- Packaging -- Quality control; Food -- Packaging